Grenada : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Grenada. (IMF Staff Country Reports; Country Report ;, 2018)
Grenada made important strides under the 2014-17 ECF-supported program, achieving an impressive debt reduction by 37 percent of GDP since 2013, upgrading the framework for fiscal policy, strengthening the financial system, improving governance, and creating a better business environment. Nonetheless, public debt is still relatively high, job creation has been insufficient, and the institutional capacity for policy implementation needs strengthening.